PENGENDALIAN PERSEDIAAN BAHAN BAKU CRUDE COCONUT OIL (CCO) PADA PT PALKO SARI EKA - Fadlillah, Siti Nur (Industrial and Systems Engineering Assessment Journal (INASEA), 2007)
Inventory system is one of the essential managerial functions because most of companies have a big investment in this aspect. PT Palko Sari Eka as an oil refinery company, uses Crude Coconut Oil as a dominant raw material to its production process activities. An optimal Inventory system is very important to be implemented by the company so that the company can provide product as customer needs and give inventory cost as more efficient.